Understanding airline travelers perceptions of well - being: the role of cognition, emotion, and sensory experiences in airline lounges - Kim, Hyeon Cheol; Chua, Bee Lia; Sanghyeop, Lee; Boo, Huey Chern; Heesup, Han (Taylor & Francis, 2016)
This study investigated the relationships among cognition, emotion, sensory, well-being perception, satisfaction, word-of-mouth, and intention to revisit airline lounges. Results of the structural analysis revealed that travelers’ overall perceptions of well-being were more dependent on the cognitive and sensory dimensions of the lounge experience, and cognitive evaluation was more influential than sensory evaluation in enhancing this perception of well-being. Our results indicated that travelers’ perceived well-being with regard to the airline lounge experience induced high levels of satisfaction. Moreover, it was identified that this perception of well-being was not enough to generate travelers’ positive word-of-mouth, but it did ensure their repatronage.